The Argon AR Web Browser and standards-based AR application environment - MacIntyre, Blair; Hill, Alex; Rouzati, Hafez; Gandy, Maribeth; Davidson, Brian (2011 10th IEEE International Symposium on Mixed and Augmented Reality, 2011)
A common vision of Augmented Reality (AR) is that of a person immersed in a diverse collection of virtual information, superimposed on their view of the world around them. If such a vision is to become reality, an ecosystem for AR must be created that satisfies at least these properties: multiple sources (or channels of interactive information) must be able to be simultaneously displayed and interacted with, channels must be isolated from each other (for security and stability), channel authors must have the flexibility to design the content and interactivity of their channel, and the application must fluidly integrate with the ever-growing cloud of systems and services that define our digital lives. In this paper, we present the design and implementation of the Argon AR Web Browser and describe our vision of an AR application environment that leverages the WWW ecosystem. We also describe KARML, our extension to KML (the spatial markup language for Google Earth and Maps), that supports the functionality required for mobile AR. We combine KARML with the full range of standard web technologies to create a standards-based web browser for mobile AR. KARML lets users develop 2D and 3D content using existing web technologies and facilitates easy deployment from standard web servers. We highlight a number of projects that have used Argon and point out the ways in which our web-based architecture has made previously impractical AR concepts possible.